Optimal Recovery of n-Linear Functionals According to Linear Information - Babenko, V. F.; Gun’ko, M. S.; Rudenko, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We determine the optimal linear information and the optimal procedure of its application for the recovery of n-linear functionals on the sets of special form from a Hilbert space.